Acquisition and Transmission of Streptococcus pneumoniae Are Facilitated during Rhinovirus Infection in Families with Children - Karppinen, Sinikka; Teräsjärvi, Johanna; Auranen, Kari; Schuez-Havupalo, Linnea; Siira, Lotta; He, Qiushui; Waris, Matti; Peltola, Ville (American journal of respiratory and critical care medicine, 2017)
Laboratory and clinical evidence suggests synergy between rhinoviruses and Streptococcus pneumoniae in the pathogenesis of respiratory tract infections. However, it is unclear whether rhinoviruses promote pneumococcal acquisition and transmission. To describe the impact of rhinovirus infection on the acquisition and transmission of pneumococci within families with children. We investigated 29 families with at least two children. The follow-up started at the onset of respiratory infectious symptoms in any family member and consisted of daily symptom diary and nasal swab samples from each participant twice per week for 3 weeks. Swabs were taken by the parents and sent to a study clinic by mail. Rhinoviruses were detected by reverse transcription-polymerase chain reaction and typed by sequencing. Pneumococci were identified by an antigen test and by standard culture methods, serotyping, and whole-genome sequencing. The effect of rhinovirus infection on the rates of pneumococcal acquisition and within-family transmission was estimated from the observed acquisition events and person-times spent uncolonized, using Poisson regression. Rhinovirus was detected in 38 subjects (30%) at the onset and in 86 subjects (67%) during the follow-up. S. pneumoniae was detected on the first day in 9 (7%) and during follow-up in 38 (30%) subjects. Children with rhinovirus infection had a 4.3-fold rate of pneumococcal acquisition from the community (95% confidence interval, 1.1-15.4) and a 14.8-fold rate of within-family transmission (95% confidence interval, 3.1-69.6) compared with children without rhinovirus infection. Rhinovirus infection within families facilitates acquisition and within-family transmission of S. pneumoniae.